2013
DOI: 10.1371/journal.pone.0081167
|View full text |Cite
|
Sign up to set email alerts
|

Cytokeratin 15 Marks Basal Epithelia in Developing Ureters and Is Upregulated in a Subset of Urothelial Cell Carcinomas

Abstract: The mammalian ureter contains a water-tight epithelium surrounded by smooth muscle. Key molecules have been defined which regulate ureteric bud initiation and drive the differentiation of ureteric mesenchyme into peristaltic smooth muscle. Less is known about mechanisms underlying the developmental patterning of the multilayered epithelium characterising the mature ureter. In skin, which also contains a multilayered epithelium, cytokeratin 15 (CK15), an acidic intermediate filament protein, marks cells whose p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 44 publications
3
19
0
Order By: Relevance
“…Basal cell carcinomas also arise from the hair follicle and more specifically from the Krt15 + cells (23). Furthermore, Krt15 also marks the ureter epithelium, and its expression is increased in a subset of urothelium cell carcinomas (24). Given its critical role in epidermal renewal, repair, and cancer development, investigation of Krt15 + cells may provide critical insights into a putative esophageal stem cell population.…”
Section: Krt15-crepr1 R26mentioning
confidence: 99%
“…Basal cell carcinomas also arise from the hair follicle and more specifically from the Krt15 + cells (23). Furthermore, Krt15 also marks the ureter epithelium, and its expression is increased in a subset of urothelium cell carcinomas (24). Given its critical role in epidermal renewal, repair, and cancer development, investigation of Krt15 + cells may provide critical insights into a putative esophageal stem cell population.…”
Section: Krt15-crepr1 R26mentioning
confidence: 99%
“…The EPR1614Y antibody has been widely used to study K15 expression as a biomarker of epidermal stem cells in scar formation 63 , differentiation of human hair follicle cells into neurons 64 , psoriatic skin lesions 50 , ameloblastoma 65 , mammary epithelium 66 , developing ureters 67 and human cornea 37 . In view of our data that EPR1614Y would react with cell cytoskeleton even when K15 is absent, some of the published work in which this antibody has been used may require reinterpretation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanisms underlying the role of HOXA7, inducing PCa to invade and metastasize, remain unclear. Woolf suggested that the KRT15 gene, encoding for CK15, might be a novel marker for urinary tract epithelial precursor cells [ 27 ]. ITGBL1 (Integrin, beta-like 1) is a β-integrin-related extracellular matrix protein and contains ten EGF-like repeats that dominate as a gene in the osteoblast-like gene-expression signature [ 28 ], which was highly expressed in ovarian cancer tissues and could promote cancer cell migration and invasion [ 29 ], and facilitated the acquisition of tumor cell advantages in recruiting, residing, and organ selectivity to the bone during breast cancer metastasis [ 28 ].…”
Section: Discussionmentioning
confidence: 99%